High Throughput CBAC Hardware Encoder With Bin Merging for AVS 2.0 Video Coding - Choi, Young-Kyu; Lee, Hyuk-Jae; Chae, Soo-Ik (IEEE transactions on circuits and systems for video technology, 2021)
Context-based binary arithmetic coding (CBAC) is an entropy coder of AVS 2.0, the latest Chinese video compression standard for 8K ultra-high-definition (UHD) video, which employs a logarithmic number system to avoid multiplication operations for range updates for binary arithmetic coding (BAE). In this paper, we propose a high-throughput CBAC hardware encoder for 8K UHD. To enhance its throughput, we introduce a bin-merging technique that converts a subsequence of bins into a merged bin without affecting the functionality of the CBAC encoder. Moreover, we also employ a 4-stage pipeline architecture for CBAC and lookup tables for context updates. Consequently, the proposed CBAC encoder can process about 3.94 bins per cycle and achieve a throughput of 2.9 Gbins per second. When synthesized in a TSMC 65nm LP process, it operates up to 735 MHz and the total gate count is 182.5 K. To the best of our knowledge, this is the highest throughput for a CBAC encoder.